Computational simulation of muscle fiber contraction: revealing the structural function of endomysium - Corral Barricarte, Miriam; Calvo Calzada, María Begoña; Grasa Orús, Jorge (Jornada de Jóvenes Investigadores del I3A, 2025)
Connective tissue is a structural support element of muscles. The endomysium is the layer that surrounds the basal and plasma membranes of muscle fibers. This study analyzes how changes in the length of two fibers connected by such tissue affect the active force during contraction, considering its anisotropic behavior.